NEW SPECIES OF EXOCHONOTUS BARR, 1980 (COLEOPTERA: CLERIDAE: ENOPUINAE) FROM CENTRAL CHILE (Acta Entomológica Chilena, 2022)
A new species of Exochonotus Barr, 1980, E. bicolor n. sp., from central Chile is described. Figures of the habitus and structures of the species are given.
Keywords: Coleóptera, Cleridae, Enopliinae, Exochonotus, new species, Chile